EULEX and the fight against organised crime in Kosovo: what’s the record? - Proksik, Joschka (Trends in organized crime)
Staffed by international police officers, prosecutors and judges, EULEX was mandated to strengthen Kosovo’s domestic rule-of-law institutions and endowed with executive authority to ensure that high-level criminal cases, including organised crime, are properly investigated and prosecuted. Yet, after more than nine years of operation, EULEX has proven largely ineffective in using its executive authority to counter organised crime and its capacity-building efforts have not led to significant local improvements in this area. Insufficient framework conditions shaped by years of impunity for politico-criminal power structures prevent capacity-building efforts from taking effect as local rule-of-law institutions remain hesitant and timid to investigate and prosecute high-level criminals. It is argued that EULEX’s own conduct and weak executive performance has severely undermined the mission’s efforts to strengthen local law enforcement through capacity-building.